Komunikasi Interaktif Guru dan Anak dalam Meningkatkan Kemampuan Bahasa Anak Usia Dini - Nur Amah; Tri Fadilah; Yulia Safutri; Marlina Marlina (CV. Alim's Publishing, 2026)
Communication is an important aspect in the development of early childhood, especially in improving language skills as a foundation for children’s social and cognitive development. Interactive communication between teachers and children creates a learning environment that encourages children to express ideas, convey feelings, and develop vocabulary through meaningful interactions. This study aims to examine the role of interactive communication between teachers and children in improving early childhood language abilities. The method used in this study is a literature review approach by analyzing various theories and previous studies related to teacher-child communication and early childhood language development. The results of the study indicate that effective interactive communication, including verbal and nonverbal communication, questioning strategies, active listening, and positive responses from teachers, can stimulate children’s speaking skills, confidence, and ability to communicate. Therefore, teachers have an important role as facilitators in creating communicative learning activities that support optimal language development in early childhood.